A bibliometric analysis of Indonesian ethnic food studies - Wargadalem, Farida R.; Nasyaya, Annada; Santoso, Anang Dwi (jurnal1, 2024)
This study examines the evolution and growth of research on ethnic cuisine in Indonesia over a thirty-year period (1993–2023) using a bibliometric analysis. The findings revealed that research in this field has grown with an average annual expansion of 6.7%. Thematic evolution highlights a shift in focus from the cultural and regional aspects of ethnic cuisine to scientific and nutritional dimensions, such as health benefits, functional foods, and modernized practices. Additionally, this study identifies key trends, including the role of gender and age in shaping food preferences, the contrasts between rural and urban dietary behaviors, and influence of globalization on traditional food systems. A trend of collaborative research was observed, with international partnerships involving nations such as Malaysia, Japan, China, and Canada underscoring the global appeal and relevance of Indonesian ethnic food research. This study highlights the growing interdisciplinary and international nature of research in this field. Recommendations for future studies include exploring diverse perspectives,  and expanding cross-national research to address the dynamic challenges and opportunities in ethnic cuisine studies.